Peningkatan Kompetensi Profesional Guru Dalam Menyusun Laporan Penelitian Tindakan Kelas Melalui Model Pembinaan CLCK (Contoh, Latihan, Control, Kerja Mandiri) Berbasis Mentoring Di SDN 03 Batang Gasan - Dasniati S.Pd (JURNAL MANAJEMEN PENDIDIKAN, 2016)
Abstract Based on observations of the competence of teachers at SDN 03 Batang lascivious in preparing the report on the school action research found that the phenomenon of professional competence of teachers in preparing classroom action research is still low. The purpose of this study is to describe and obtain information about the increase of professional competence of teachers in preparing classroom action research reports through coaching model Clck (Example, Exercise, Control, Self-Employment) based mentoring in SDN 03 Batang Gasan. This research is a school action. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 9 The teachers at SDN 03 Batang lascivious. Data were collected by using observation sheet. Data were analyzed using percentages. Based on the results of research and discussion, we can conclude that Clck coaching model based mentoring can improve the ability of teachers in preparing classroom action research report in SDN 03 Batang lascivious. Analysis of the quality of PTK statements made by teachers indicated that the professional competence of teachers in preparing classroom action research reports increased from the first cycle to the second cycle. Professional competence of teachers in preparing classroom action research report on the first cycle was 77.69 (enough) increased to 84.69 (both) on the second cycle with an increase of 7.00 points.Keywords: Teacher Professional Competence, Reports PTK, Clck coaching model based mentoring.